Absolute quantification of olive oil DNA by droplet digital-PCR (ddPCR): Comparison of isolation and amplification methodologies. (15th December 2016) - Scollo, Francesco; Egea, Leticia A.; Gentile, Alessandra; La Malfa, Stefano; Dorado, Gabriel; Hernandez, Pilar
Highlights: Defining the origin of olive oil represents a key aspect to ensure product traceability. DNA quality is often unsatisfactory and its absolute quantification may not be possible. Different DNA extraction protocols were evaluated by qRT-PCR and ddPCR. Qualitative aspects and amplified DNA's copies number were quantified. Abstract: Olive oil is considered a premium product for its nutritional value and health benefits, and the ability to define its origin and varietal composition is a key step towards ensuring the traceability of the product. However, isolating the DNA from such a matrix is a difficult task. In this study, the quality and quantity of olive oil DNA, isolated using four different DNA isolation protocols, was evaluated using the qRT-PCR and ddPCR techniques. The results indicate that CTAB-based extraction methods were the best for unfiltered oil, while Nucleo Spin-based extraction protocols showed greater overall reproducibility. The use of both qRT-PCR and ddPCR led to the absolute quantification of the DNA copy number. The results clearly demonstrate the importance of the choice of DNA-isolation protocol, which should take into consideration the qualitative aspects of DNA and the evaluation of the amplified DNA copy number.